CONSTITUTIVELY ACTIVATED TYROSINE KINASE INHIBITOR DRUG DESIGN: HOMOLOGY MODELING AND DOCKING STUDIES ON CHRONIC MYELOGENOUS LEUKEMIA BCR-ABL FUSION PROTEIN - ASHISH JAIN; ABHISHEK SENGUPTA; PRIYANKA NARAD (International Journal of Pharma and Bio Sciences, 2015)
Constitutively activated tyrosine kinase is a sole reason for chronic myelogenous leukemia (CML) in humans. Normal tyrosine kinase is responsible for phosphorylation, which support division of white blood cell .After reciprocal translocation between 9th and 22nd chromosome a fusion protein called constitutively activated tyrosine kinase are formed which increase the number of white blood cell and cause leukemia. Currently this constitutively activated tyrosine kinase are inhibited by tyrosine kinase inhibitor such as imatinib and dasatinib but a low remission rate force to search for a novel tyrosine kinase inhibitor. In the present work homology modeling of the fusion protein was done and actively inhibited by phytoligands. Docking analysis of various phytoligands on the active sites of modelled fusion protein were performed and the phytoligand which shows minimum energy hence maximum stability was selected and considered as a novel inhibitor for constitutively activated tyrosine kinase. Docking of modeled protein with the previously used drug was also performed to confirm the maximum stability of chosen phytoligand 1, 3-Diacetylvilasinin with (molDocscore -163.768) with the fusion protein. The results reveal that virtual screening of phytoligands is a very promising area which could lead to the discovery of the potent drug compound. This computational predicted data could be further validated using suitable assays for further consideration.